Geography, Poverty and Conflict in Nepal - Do, Quy-Toan (2012)
We conduct an empirical analysis of the geographic, economic, and social factors that contributed to the spread of civil war in Nepal over the period 1996-2006. This within-country analysis complements existing cross-country studies on the same subject. Using a detailed dataset to track civil war casualties across space and over time, several patterns are documented. Conflict-related deaths are significantly higher in poorer districts and in geographical locations that favor insurgents, such as mountains and forests; a 10 percentage point increase in poverty is associated with 25-27 additional conflict-related deaths. This result is similar to that documented in cross-country studies. In addition, the relationship with poverty and geography is similar for deaths caused by the insurgents and deaths caused by the state. Furthermore, poorer districts are likely to be drawn into the insurgency earlier, consistent with the theory that a lower cost of recruiting rebels is an important factor in starting conflict. On the other hand, geographic factors are not significantly associated with such onset, suggesting that they instead contribute to the intensity of violence only after conflict has started. Finally, in contrast to some cross-country analyses, ethnic and caste polarization, land inequality, and political participation are not significantly associated with violence.